Effects of ultrasonic surface rolling and plasma nitriding on microstructure and properties of 690TT alloy. (18th January 2022) - Chen, Baoquan; Liu, Junbiao; Li, Xiaoxian; Chen, Weiqing; Zhang, Xuehui; Liang, Tongxiang
Abstract: To enhance surface mechanical properties of 690TT alloy, a surface hardening layer was obtained by ultrasonic surface rolling treatment (USRT) and plasma nitriding (PN). The surface morphology, mechanical properties, wear performances and corrosion performance were investigated by XRD, TEM, using a hardness tester, tensile tester, wear tester and electrochemical workstation in simulated sea water, respectively. The results showed that USRT as the pre-treatment can strengthen the performance of PN treatment samples. The USRT + PN treated sample showed existence of dislocation tangles and twin grains. Corrosion resistance in simulated sea water was enhanced. The surface microhardness increased by 180% compared with the untreated sample, the cross-sectional hardness gradually decreased till the depth of 1 mm. The tensile strength increased by a factor of 90% while the elongation decreased by only 40%. The wear scar was narrower and shallower than the untreated sample and the wear rate was significantly dropped. This paper aims at providing a new method for surface strengthening of 690TT alloy.